2009
DOI: 10.1001/archsurg.2009.111
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for Blunt Cerebrovascular Injuries

Abstract: With an overall CVA risk of 21% and a documented latent period, comprehensive screening, early diagnosis, and institution of antithrombotic therapy for BCVI are clearly warranted. The type of treatment, heparin vs antiplatelet agents, does not appear to affect either stroke risk or injury healing rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…There have been efforts to construct evidence-based guidelines for treating BCVI patients [5,9,31]. According to guidelines, the indication criteria for computed tomography angiography (CTA) of cervical arteries would use extended Denver protocol, which includes signs and symptoms for BCVI, e.g., focal neurological deficit, expanding cervical hematoma, neurological deficit inconsistent of head computed tomography (CT), and stroke on CT/magnetic resonance imaging (MRI), or risk factors of BCVI, e.g., high-energy trauma, facial fractures, CSI, and TBI with thoracic injuries [9,13,14]. If these conditions are satisfied, the patient should go through CT angiography, and if BCVI is found, an antithrombotic treatment should be started as early as possible for minimum of 3 months.…”
Section: This Article Is Part Of the Topical Collection On Brain Traumamentioning
confidence: 99%
“…There have been efforts to construct evidence-based guidelines for treating BCVI patients [5,9,31]. According to guidelines, the indication criteria for computed tomography angiography (CTA) of cervical arteries would use extended Denver protocol, which includes signs and symptoms for BCVI, e.g., focal neurological deficit, expanding cervical hematoma, neurological deficit inconsistent of head computed tomography (CT), and stroke on CT/magnetic resonance imaging (MRI), or risk factors of BCVI, e.g., high-energy trauma, facial fractures, CSI, and TBI with thoracic injuries [9,13,14]. If these conditions are satisfied, the patient should go through CT angiography, and if BCVI is found, an antithrombotic treatment should be started as early as possible for minimum of 3 months.…”
Section: This Article Is Part Of the Topical Collection On Brain Traumamentioning
confidence: 99%
“…Studies reporting on initially asymptomatic patients treated with antiplatelet agents indicate a risk of stroke of up to 11% [10, 12, 21, 26, 31, 32, 33, 34, 36]. Studies reporting on initially asymptomatic patients treated with anticoagulation indicate a risk of stroke of up to 20% [10, 32].…”
Section: Mechanism and Risk Of Ischemic Strokementioning
confidence: 99%
“…Furthermore, antiplatelet agents carry a theoretical advantage in that the mechanism of stroke in TCVI is usually artery-to-artery embolism, and antiplatelet agents may be more appropriate in the platelet-rich arterial environment. Several retrospective studies have suggested that antiplatelet therapy is equivalent to anticoagulation in terms of neurological outcomes [10, 36, 42]. …”
Section: Antithrombotic Therapymentioning
confidence: 99%
“…4,5 As a result, growing treatment trends have patients who present with cervical spine trauma screened for cerebrovascular injury before surgical stabilization of the spine so that treatment can be started early. 2,6,7 Cerebrovascular injury can lead to neurovascular complications either from thrombus formation at the tear site or narrowing of the vessel. 8 Anticoagulation treatment begun in the early period (before the onset of stroke symptoms) has been shown to improve mortality and lower neurologic complications, but in patients having spinal surgery it carries the risk of epidural hematoma and major bleeding.…”
Section: Introductionmentioning
confidence: 99%